An extraordinary case of oral leukocytoclastic vasculitis demonstrating igd deposition around dermal vessels and within mucosal keratinocytes - Ana Maria Abreu-Velez; Bruce R. Smoller; Michael S. Howard (Our Dermatology Online, 2021)
Cutaneous vasculitides include a widespread and heterogeneous cluster of diseases affecting the blood vessels that are clinically characterized by polymorphic skin lesions, including palpable purpura, urticarial and/or necrotic-ulcerative lesions. Often, they can be manifestations of a systemic disease. Selected cases occur in the mouth. A 75-year-old female presented to her physician for the sudden appearance of blisters in her mouth, with severe orodynia and no history of other diseases or medication intake. A skin biopsy of the oral mucosa yielded a diagnosis of leukocytoclastic vasculitis. The direct immunofluorescence and immunohistochemistry stains demonstrated deposits of IgD, IgG, IgA, IgM, kappa, lambda, C1q, C3c, albumin and fibrinogen at the upper dermal neurovascular plexus. IgD also demonstrated positive nucleolar staining of the keratinocytes. Our case involves a rare presentation of oral cutaneous vasculitis with immune deposits of several immunoglobulins, complement, albumin and fibrinogen. Our case adds importance to studies of the IgD role in antigenic complex immune responses, especially in the mouth.